Spatial distribution of heavy metal lead concentration in soil and mangrove plants in the mangrove forests of Surabaya City: a case study of Gunung Anyar and Wonorejo mangroves - Aditya, Haidar Fari; Sholikah, Dinna Hadi; Pazi, Ahmad Mustapha Mohamad; Permatasari, Fina Dwi (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE), 2025)
Mangrove forests are vital coastal ecosystems that provide shoreline protection, support biodiversity, and sequester carbon. However, urbanization and industrial activities have led to the introduction of heavy metal contaminants, especially lead (Pb), posing significant threats to ecosystem health. This study examines Pb concentration in Gunung Anyar and Wonorejo mangroves in Surabaya, two key areas for coastal defence that are increasingly exposed to Pb pollution. From January to March 2024, samples were collected from sediments, roots, and leaves of Avicennia marina, Rhizophora mucronata, and Bruguiera gymnorrhiza using purposive random sampling at nine observation points. Pb content was analyzed using Atomic Absorption Spectrophotometry and spatial analysis of Pb distribution analysis using ArcGIS 10.8. The results showed that Pb concentrations were highest in Gunung Anyar, reflecting the impact of industrial activities, with the highest Pb levels found in soil (14.22 ppm), roots (1.57 ppm), and leaves (2.21 ppm) of Avicennia marina. Soil pH, electrical conductivity, organic matter, and clay content were identified as key factors influencing Pb uptake and retention, with neutral pH and higher organic matter supporting greater Pb accumulation. The study emphasizes the role of mangrove ecosystems in bioremediation, highlighting their potential to mitigate coastal pollution through phytoremediation. This research underscores the importance of monitoring and conserving mangrove ecosystems to enhance their role in pollution management and coastal health.